Exploring the relationship between tax compliance costs and compliance issues in Malaysia - Abdul Jabbar, Hijattulah; Pope, Jeff (Applied Law and Policy (ALAP) Area of Research Focus (AoRF), 2008)
This study estimates the income tax compliance costs, and measures possible noncompliance behaviour, from a business managerial perspective in Malaysia.The findings reported in this paper are part of a larger nationwide mail survey into corporate Malaysian small and medium enterprises (SMEs) under the income tax self-assessment system.The findings show that a relatively greater number of SMEs are being compliant in terms of income reporting and accuracy in their deductions.The investigation into the relationship between the size of tax compliance costs and likely compliance behaviour indicates no statistical significance. Possible reasons for these findings are presented.